2012
DOI: 10.4103/0974-2700.99685
|View full text |Cite
|
Sign up to set email alerts
|

Can glasgow score at discharge represent final outcome in severe head injury?

Abstract: Background:Patients with head injury continue to improve over time and a minimum follow-up of six months is considered necessary to evaluate outcome. However, this may be difficult to assess due to lack of follow-up. It is also well known that operated patients who return for cranioplasty usually have the best outcome.Aims and Objectives:To assess the outcome following severe head injury using cranioplasty as a surrogate marker for good outcome.Materials and Methods:This was a retrospective study carried out f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Another reason for the low percentage of this group is their frequent habit of early self-discharge before proper records are taken. The overall mortality rate of 21.2% and the mortality rate of 57.9% in severe head injuries are similar to other studies conducted in Nigeria, Kenya, Benin and India (18, 19, 21, 23, 25). Initial GCS and pupilary reaction have been identified as valid outcome predictors in this study like in many other studies (17, 18).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another reason for the low percentage of this group is their frequent habit of early self-discharge before proper records are taken. The overall mortality rate of 21.2% and the mortality rate of 57.9% in severe head injuries are similar to other studies conducted in Nigeria, Kenya, Benin and India (18, 19, 21, 23, 25). Initial GCS and pupilary reaction have been identified as valid outcome predictors in this study like in many other studies (17, 18).…”
Section: Discussionsupporting
confidence: 87%
“…This shows that further treatment after discharge is needed. Outcome improvement of severe head injury patients is not only about enhancing acute care but providing rehabilitation facilities (19). …”
Section: Discussionmentioning
confidence: 99%
“…Hence, the factors predicting outcome in the present study were analyzed for their short-term GOS at discharge rather than analyzing the follow-up GOS that was only available in a limited subgroup. The assumption used here was that there is usually no statistical difference between GOS at discharge and at a follow-up at 6 months as shown in a study by Agrawal et al [23] In a retrospective cohort of 55 patients with severe head injury, Pompucci et al, [24] showed that age >65 years and a poor GCS (3)(4)(5) at presentation were adversely associated with the functional outcome in TBI patients undergoing a DC. Similarly, Hukkelhoven et al, [6] performed a meta-analysis of 5,600 patients with severe TBI, and found that the association between the patient's age and outcome is a continuous one that is inversely related.…”
Section: Discussionmentioning
confidence: 95%
“…We found that total number of cases treated surgically was 17 cases (28.3%) and 43 cases (71.6%) were treated conservatively. According to outcome 36 cases (60%) were alive and 24 cases (40%) died, all cases managed in ICU, figures (1,2).…”
Section: Resultsmentioning
confidence: 99%
“…So the lower GCS, the more chance for surgical treatment and the worst outcome. Perel et al (2008) and Agrawal et al (2012) considered that GCS after full resuscitation was one of the most important predictor factor of outcome after TBI. Baum J. et.al.…”
Section: Discussionmentioning
confidence: 99%